Photographic Estimation of Arch Height of Adult Bangladeshi Male - Parash, M Tanveer Hossain; Naushaba, Humaira; Rahman, Md Ashfaqur; Shimmi, Sadia Choudhury (Bangladesh Journal of Anatomy, 2013)
Context: The height of the medial longitudinal arch of the foot is commonly thought to be a predisposing factor to injuries. High-arched runners exhibit more bony, ankle and lateral injuries but low-arched runners reveal a higher risk of soft tissue, knee and medial injuries. Moreover high-arched and low-arched people have greater rearfoot eversion excursions than those with normal arch structure. So, it is important to have relatively easy and reliable way to measure the height of foot arch. The most reliable and valid way of measuring the foot arch is by the arch height index measurement system (AHIMS). The AHIMS can be costly to buy or construct for a third world country like Bangladesh. An alternative idea developed recently involved the use of digital photography to assess the arch height. Study design: Cross sectional, analytical type of study. Place and period of the study: Department of Anatomy, Sir Salimullah Medical College, Dhaka from July 2010 to June 2011. Materials and Method: A total number of 110 medical students of 3rd and 4th year were chosen by purposive sampling. Results: The values of arch height were 6.04 cm to 8.78 cm in sitting position and 4.83 cm to 7.03 cm in standing position respectively. DOI: http://dx.doi.org/10.3329/bja.v10i2.17284 Bangladesh Journal of Anatomy, July 2012, Vol. 10 No. 2 pp 59-62